CHARACTERIZATIONS OF REGULAR ABEL-GRASSMANN’S GROUPOIDS BY THE PROPERTIES OF THEIR (∈,∈ ∨q\(_k\))-FUZZY IDEALS - Ma, Xueling; Zhan, Jianming; Khan, Madad; Aziz, Tariq (Italian Journal of Pure and Applied Mathematics, 2014)
In this paper, we characterize some properties of regular Abel-Grassmann’s groupoid in terms of its (∈, ∈ ∨qk)-fuzzy ideals. (pp. 309-324)